Fuel Cell Electrodes Based on Carbon Nanotube/Metallic Nanoparticles Hybrids Formed on Porous Stainless Steel Pellets - S. M. Khantimerov; E. F. Kukovitsky; N. A. Sainov; N. M. Suleimanov (International Journal of Chemical Engineering)
The preparation of carbon nanotube/metallic particle hybrids using pressed porous stainless steel pellets as a substrate is described. The catalytic growth of carbon nanotubes was carried out by CVD on a nickel catalyst obtained by impregnation of pellets with a highly dispersive colloidal solution of nickel acetate tetrahydrate in ethanol. Granular polyethylene was used as the carbon source. Metallic particles were deposited by thermal evaporation of Pt and Ag using pellets with grown carbon nanotubes as a base. The use of such composites as fuel cell electrodes is discussed.